2014
DOI: 10.5815/ijcnis.2014.09.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maintenance on Computer Network Reliability

Abstract: At the time of the new information technologies, computer networks are inescapable in any large organization, where they are organized so as to form powerful internal means of communication. In a context of dependability, the reliability parameter proves to be fundamental to evaluate the performances of such systems. In this paper, we study the reliability evaluation of a real computer network, through three reliability models. The computer network considered (set of PCs and server interconnected) is localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Horenbeek & Pintelon (2013) presented a dynamic predictive maintenance policy that reduces long-term maintenance cost per unit time in multi-component systems while considering different component dependencies (i.e., structural, economic and stochastic dependence) [50].To determine the performance of the dynamic predictive maintenance policy, a numerical example was compared to five other traditional maintenance policies based on minimal mean maintenance costs per unit time while considering different component dependencies. The traditional maintenance policies are: continuous condition-based maintenance, age-based maintenance, age-based maintenance with grouping, block-based maintenance, and inspection condition-based maintenance [50][51][52][53][54].…”
Section: Related Workmentioning
confidence: 99%
“…Horenbeek & Pintelon (2013) presented a dynamic predictive maintenance policy that reduces long-term maintenance cost per unit time in multi-component systems while considering different component dependencies (i.e., structural, economic and stochastic dependence) [50].To determine the performance of the dynamic predictive maintenance policy, a numerical example was compared to five other traditional maintenance policies based on minimal mean maintenance costs per unit time while considering different component dependencies. The traditional maintenance policies are: continuous condition-based maintenance, age-based maintenance, age-based maintenance with grouping, block-based maintenance, and inspection condition-based maintenance [50][51][52][53][54].…”
Section: Related Workmentioning
confidence: 99%
“…To optimize maintenance policy, knowledge of the system lifetime is essential, for this, a study on the reliability of this system has previously been made (Oudjedi Damerdji & Noureddine, 2014) and the final result indicated that the Exponential distribution is suited for the computer system reliability and that is why the Exponential Alert Delay model has been chosen for this present study. The failure rate of the system not maintained has been estimated to λ(t) = 0.00014437 failures per second.…”
Section: Specification Of the Systemmentioning
confidence: 99%